Employment of University Graduates Across the Post-soviet Space: Problems and Solutions (The Example of Kazakhstan) - Fursova, Valentina Vladimirovna; Shakirova, Alla Yuriyevna; Nikitina, Tatyana Nikolaevna; Spirchagova, Tatyana Anatolevna; Syzdykova, Machpal (Journal of History Culture and Art Research, 2017)
The article analyzes the prospects of work search by the graduates of higher educational institutions across the post-Soviet space using the example of the Republic of Kazakhstan. Currently, the problem of the employment selection strategy among the graduates of the post-Soviet space countries remains as a priority. Graduated experts at the labor market experience a complex of institutional problems: a small number of jobs, bureaucratization, inadequate knowledge for vacant posts, the lack of infrastructure at higher education institutions for the interaction with enterprises. All this leads to the dissatisfaction of specialists with their professional and social status, to the choice of a work place which does not correspond an acquired specialty, or to the use of personal ties of their family to the detriment of their own desires and qualifications, and, consequently, to the reproduction of disproportions in the economy. As a research in the field of economic sociology, the article relies on conflictological and structural-functional paradigms. A questionnaire is used to reveal the research topic. The objectives of the study are the following ones: the problems of graduate employment and the ways of their solution in Kazakhstan. The result of the conducted research showed that the successful adaptation of graduates at the labor market makes it necessary to develop and introduce effective educational programs in the teaching process, including practical-oriented disciplines that give the opportunity to obtain knowledge required by employers. The students of senior courses should study practical courses, preferably on practice bases, they should actively participate in the development and the implementation of specialized projects, grants, in scientific competitions, conferences, which will allow them to develop creative thinking, to understand the content of future profession, to master the basic theoretical and practical material.